2019
DOI: 10.5539/jas.v11n15p153
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination and Initial Growth of Quinoa Seedlings Under Water and Salt Stress

Abstract: Excessive amounts of salts and soil water deficiency interfere on seed germination and the full development of several crops. The objective of this research was to evaluate the effect of water stress and salinity on the germination process and initial growth of quinoa (Chenopodium quinoa Willd.) seedlings. In the first experiment, two quinoa seed lots with different physiological conditions were distributed on paper soaked in aqueous solution containing polyethylene glycol PEG-6000 in osmotic potentials corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In another study with four distinct osmotic agents (CaCl 2 , KCl, MgCl 2 , and NaCl), Stefanello et al (2019) concluded that chia seeds (Salvia hispanica L.) were sensitive to exposure to different salts with osmotic potential between -0.1 and -0.4 MPa, which was observed by decreased germination and vigor. Similarly, Barbieri et al (2019) found that the progressive reduction in osmotic potential induced by NaCl, KCl, CaCl 2 and MgCl 2 salts negatively affected seed germination and initial growth of quinoa seedlings (Chenopodium quinoa Willd. ).…”
Section: Resultsmentioning
confidence: 92%
“…In another study with four distinct osmotic agents (CaCl 2 , KCl, MgCl 2 , and NaCl), Stefanello et al (2019) concluded that chia seeds (Salvia hispanica L.) were sensitive to exposure to different salts with osmotic potential between -0.1 and -0.4 MPa, which was observed by decreased germination and vigor. Similarly, Barbieri et al (2019) found that the progressive reduction in osmotic potential induced by NaCl, KCl, CaCl 2 and MgCl 2 salts negatively affected seed germination and initial growth of quinoa seedlings (Chenopodium quinoa Willd. ).…”
Section: Resultsmentioning
confidence: 92%
“…In response to salt stress, production of ROSs, as singlet oxygen, superoxide, hydroxyl radical, and hydrogen peroxide, is enhanced (Gupta and Huang, 2014;Du et al, 2015;Kaiser et al, 2016; leading to oxidative damage in various cell components, such as proteins, lipids, and DNA, interrupting vital cell functions of the plants (Liu et al, 2018;). In addition, the high concentration of Na + inhibits capture of K + ions, which is an essential element for growth, and this results in lower yield and may even lead to death (Barbieri et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in salinity brings about changes in plant capacity in taking up, transporting, and using the ions necessary for plant development and reduces the activity of enzymes responsible for respiration and photosynthesis (Gupta et al, 2014;Du et al, 2015;Silva et al, 2019). Thus, obtaining energy for development and differentiation of cells in plant tissue is restricted (Kaiser et al, 2016;Barbieri et al, 2019;Silva et al, 2019). Consequently, knowing how forage plant seeds respond under these conditions is important, especially because of the strong expansion of this crop in various regions of Brazil and around the world, not only for raising livestock but also for intercropping and in providing straw cover in the no-till system (ABIEC, 2019; ABRASEM, 2018).…”
Section: Journal Of Seedmentioning
confidence: 99%
“…One of the methods used to determine plant tolerance to water stress is assessment of the germination capacity of seeds under water restriction with polyethylene glycol (PEG), which is an effective technique since this inorganic compound reduces the osmotic potential of the solution and conducts controlled restriction in seed imbibition without causing toxicity (Pereira et al, 2012;Barbieri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation